The socio-cultural dimensions of community-based sustainability: Implications for transformational change - Axon, Stephen (Journal of Cleaner Production, 2020)
There is substantial difficulty with effectively, and meaningfully, engaging the public with community-based sustainability projects as a method to facilitate sustainable lifestyles. Individuals engage with community projects in numerous ways: cognitively (knowledge), affectively (emotions), and behaviourally (actions). One prevalent consideration that individuals consider is other peoples’ (lack of) engagement; given that the success of community-based approaches addressing climate change is dependent upon the actions, and participation, of all local residents. Findings from focus groups in seven urban communities in the UK are presented that illustrate clear elements of ‘Othering’ as part of individual engagements with community-based sustainability projects. Primarily, there is substantial consideration towards what other people within the community know, feel, and do to engage with community-based projects. Residents distinguish themselves in opposition to those they view as engaging, and not engaging, in the same way as themselves and indicate the need for equitable participation amongst all residents. These considerations have the potential to project particular barriers on wider community engagement if left to develop, cause tension, and are not resolved. Implications for participatory strategies to meaningfully and effectively engage individuals with community-based sustainability and transformational change are outlined. Insights into how considerations of ‘Othering’ can be overcome so as not to cause negative engagements with other residents and attempts to live sustainably as part of a community approach are illustrated. © 2020
Keywords: Climate change; Communities; Community based approach; Community engagement; Community project; Community-based; Community-based projects; Local residents; Othering; Public engagement; Sustainability project; Sustainability science; Sustainable development; Sustainable lifestyles; Transformational change; Transformations; Urban community; dept.egm; peer-reviewed